Epigraphy in the digital age : opportunities and challenges in the recording, analysis and dissemination of inscriptions - Velázquez, Isabel; Espinosa, David (Archaeopress Archaeology, 2021)
This volume presents epigraphic research using digital and computational tools, comparing the outcomes of both well-established and newer projects to consider the most innovative investigative trends. Papers consider open-access databases, SfM Photogrammetry and Digital Image Modelling applied to textual restoration, Linked Open Data, and more.